Equipment modification to enhance physical education learning in under-resourced elementary schools: a school action research study - Supri Yadi; Rambat Nur Sasongko; Bayu Insanistyo (Indonesian Institute for Counseling, Education and Theraphy (IICET), 2026)
Limited physical education (PE) facilities hinder active learning in many elementary schools, particularly in developing regions. This study aimed to improve the availability and utilization of physical education facilities through equipment modification in an elementary school in Seluma, Indonesia. A qualitative school action research design was employed over two cycles consisting of planning, action, observation, and reflection. The participants included one physical education teacher and 28 elementary school students selected purposively. The intervention involved modifying learning equipment using simple materials such as stones, PVC pipes, cardboard, and sand. Data were collected through observation, interviews, and documentation, and analyzed using thematic analysis. The results showed that equipment modification significantly increased the availability of facilities from low to good levels. Student participation improved from low to high, and learning motivation also increased from low to high across the research cycles. These findings indicate that equipment modification is a feasible, low-cost strategy that can improve the effectiveness of physical education learning in resource-limited schools. This study contributes to the development of innovative and sustainable teaching practices. Future research should examine the long-term impact and broader applicability of this approach.